A Useful Maneuver to Simplify Sellar Floor Repair Following Endoscopic Transnasal Pituitary Surgery - Iannelli, Aldo; Lenzi, Riccardo; Muscatello, Luca (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
The watertight closure of the skull base after endonasal surgery is and has always been critical in cranial base surgery. Nowadays, endoscopic transsphenoidal surgery is the standard of treatment for most of the sellar tumors. Reconstruction of the sella is not always deemed necessary, and generally it is reserved for patients with macroadenomas or with intraoperative evidence of cerebrospinal fluid leak. We herein report our experience with a simple maneuver that, in our opinion, simplifies sellar floor reconstruction.
Keywords: endoscopy; pituitary adenoma; transsphenoidal approach; sellar floor reconstruction.